GARCINIA COWA ROXB. ETHANOL EXTRACT INHIBITS INFLAMMATION IN LPS-INDUCED RAW 264.7 MACROPHAGES - DEWI, IRENE PUSPA; WAHYUNI, FATMA; ALDI, YUFRI; DACHRIYANUS (International Journal of Applied Pharmaceutics, 2023)
Objective: The purpose of this study was to examine the effect of Garcinia cowa Roxb. Ethanol (EGC) extract in LPS-induced Raw 264.7 macrophages by observing the release of Tumor Necrosis Factor (TNF) and Interleukin-6 (IL-6). Methods: Using the MTT method, a cell viability assay was performed to observe the cytotoxic effect on Raw 264.7 macrophages. For 24 h, Raw 264.7 macrophages were incubated with various EGC concentrations (100, 50, 10, 1 and 0.1 µg/ml). The medium was taken out after 48 h of incubation, and 100 µl of MTT 0.5 mg/ml was then added. 100 µl DMSO was used to dissolve the crystals and absorbance was measured using a microplate reader. To investigate the activity of EGC to LPS-induced Raw 264.7 macrophages, the ELISA method was used. Supernatant was obtained after treating Raw 264.7 macrophages with complete medium, EGC samples, and LPS (10 g/ml) for 24 h. IL-6 and TNF-α levels were assessed using supernatants with ELISA kit. Results: Cytotoxic effect of EGC to Raw 264.7 macrophages occurred at a concentration of 100 µg/ml with the cell viability value of 59.5%. At a concentration of 50 µg/ml, no cytotoxic effect occurred and the cell viability value was 105.5%. So, the higher concentration of EGC used for further investigation is 50 µg/ml. It was shown that the production of IL 6 was suppressed by EGC at a concentration of 12.5 µg/ml. The inhibition of TNF-α production was only seen at the concentration of 12.5, 25 and 50 µg/ml; there was an increase of TNF-α production. Conclusion: It can be concluded that EGC can be developed as a natural immunomodulator that can inhibit inflammation by suppressing IL-6 production to prevent immune system disorders.